2019
DOI: 10.1094/pdis-02-19-0271-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New QTL Contributing to Barley Yellow Dwarf Virus-PAV (BYDV-PAV) Resistance in Wheat

Abstract: Barley yellow dwarf (BYD) is a major virus disease which dramatically reduces wheat yield. Introducing BYD resistance genes into commercial varieties has been proven to be effective in reducing damage caused by barley yellow dwarf virus (BYDV). However, only one major resistance gene is readily deployable for breeding; Bdv2 derived from Thinopyrum intermedium is deployed as a chromosomal translocation. In this study, a double haploid (DH) population was developed from a cross between XuBYDV (introduced from Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…DNA extraction and genotyping were performed as described in previous publications [ 57 ]. Two parental varieties and 154 DH lines were genotyped with DArTSeq ( http://www.diversityarrays.com/ ).…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction and genotyping were performed as described in previous publications [ 57 ]. Two parental varieties and 154 DH lines were genotyped with DArTSeq ( http://www.diversityarrays.com/ ).…”
Section: Methodsmentioning
confidence: 99%
“…To date, most breeding efforts have been directed to the identification of viral tolerance, also known as 'field resistance', that refers to the ability of the plant to yield under BYD infection and is associated with a reduction of symptoms of infection independent of the virus titer (Foresman et al 2016). Field resistance has been reported to be polygenic, falling under the quantitative resistance class, where several genes with very small effects control the resistance response (Qualset et al 1973, Cisar et al 1982Ayala et al 2002;Choudhury et al 2019a;c).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the four known resistance genes, other genomic regions associated with BYD resistance have been identified through genetic mapping. These regions have been described on nearly all wheat chromosomes but have not been genetically characterized (Ayala et al 2002;Jarošová et al 2016;Choudhury et al 2019a;b;c). Moreover, two recent studies have reported that some of these new genomic regions display additive effects (Choudhury et al 2019a;b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in wheat DH production have resulted from co-culture with ovaries [11] and n-butanol treatment [12,13]. Approximately 90% of the DH lines developed in our program are destined for plant breeding companies, with the remaining populations used for research projects throughout Australia [14,15]. Genotype variability in key production parameters, such as embryo production, green plant regeneration and chromosome doubling, is an ongoing challenge, especially for the high-throughput production of breeding populations.…”
Section: Introductionmentioning
confidence: 99%